Determination of fundamental parameters and circumstellar properties for a sample of B[e] stars - Muratore, María Florencia (2011)
We develop a simple model to derive theoretical continuum energy distributions for B[e] stars, consisting of a B star surrounded by an envelope made of gas and dust. We select a sample of B[e] objects for which we construct the observed energy distributions, from 0.1 to 100 μm, using available photometric and spectroscopic data. We present some preliminary fittings.